Can Advertising Copy Make FSI Coupons More Effective? - Leclerc, France; Little, John D. C. (Journal of Marketing Research, 1997)
Packaged goods manufacturers distribute cents-off coupons in freestanding inserts (FSIs) in newspapers. Free-standing insert coupons are typically composed of two parts: the coupon per se and a print advertisement. Using two laboratory experiments and a separate analysis of coupon measurements from scanner panels, the authors investigate whether the content of the print advertisement influences the effectiveness of the coupon. Theoretical arguments suggest that the impact on consumer attitudes will depend on the executional cues of the copy, the brand loyalty of the consumers, and the consumer's involvement with the product category. The results support the theoretical framework and suggest that it is possible to make FSI coupons more effective by choosing appropriate executional cues for their advertising copy.